Low free silicon silicon carbide micro powder and preparation method and application thereof

CN122685078BActive Publication Date: 2026-10-09LIANYUNGANG WOXIN HIGH-TECH MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611152098.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-09
Estimated Expiration
2046-07-31

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种低游离硅碳化硅微粉及其制备方法与应用,以解决现有技术中碳化硅微粉游离硅含量偏高、颗粒形貌不规则、高纯化后颗粒表面能升高导致硬团聚、缺乏针对绝缘导热等高端应用场景的系统性制备方案,从而无法同时满足高绝缘、高导热、高温烧结洁净晶界及高端半导体加工等多场景严苛应用要求的技术问题

Benefits of technology

[0041] 1. A step-by-step directional removal process is used to remove free carbon by flotation, free silicon and metal impurities by acid washing, and free silicon dioxide by alkaline washing. Each step is targeted at the chemical properties of different impurity phases to achieve directional removal. The process has strong synergy and reduces the free silicon content to below 0.1wt%, preferably to below 0.05wt%. Compared with the existing single acid washing or acid-alkali washing process, the impurity removal efficiency is higher and the product purity index is more stable, which meets the stringent purity requirements of various scenarios such as high insulation and thermal conductivity interface materials, high performance sintered ceramics and semiconductor processing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of inorganic nonmetallic materials, in particular to low-free-silicon silicon carbide micro powder as well as a preparation method and application thereof, the silicon carbide micro powder comprises a silicon carbide main phase, the content of the silicon carbide in the silicon carbide main phase is not less than 98.5 wt%, and the content of free silicon is not more than 0.1 wt%. The low-free-silicon silicon carbide micro powder provided by the application fundamentally eliminates the semiconductor conductivity risk of free silicon, enables the silicon carbide micro powder to simultaneously realize high insulation and high thermal conductivity synergic performance with volume resistivity not less than 10 12 Ω*cm and thermal conductivity not less than 3 W / (m*K) at a high filling amount when the silicon carbide micro powder is used as a heat-conducting filler, breaks the technical bottleneck that ordinary silicon carbide micro powder is difficult to simultaneously realize high thermal conductivity and high insulation due to free silicon, and provides a reliable filler solution for high-end electronic packaging materials such as power semiconductor module potting glue and heat-conducting gaskets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic non-metallic materials technology, specifically to a low-free-silicon silicon carbide micropowder, its preparation method, and its application. Background Technology

[0002] Silicon carbide (SiC) micropowder is a high-hardness inorganic non-metallic material primarily bonded by covalent bonds, with a Mohs hardness of 9.5. It possesses high thermal conductivity, excellent chemical stability, and wide bandgap semiconductor properties, making it widely applicable in high-performance ceramic sintering, semiconductor wafer processing, high-insulation and thermally conductive interface materials, and metal-based composite materials. Industrially prepared silicon carbide raw materials typically contain residual free silicon, free carbon, free silica, and metallic impurities such as iron, aluminum, calcium, and magnesium, in addition to the silicon carbide main phase. Free silicon is a key impurity phase affecting the performance of silicon carbide micropowder applications: In high-performance sintered ceramics applications, free silicon melts at sintering temperatures above 1400℃, forming a grain boundary glass phase, leading to a decrease in the high-temperature strength of the ceramic and grain boundary brittleness; in high-insulation and thermally conductive interface materials applications, free silicon is a semiconductor phase with a conductivity far higher than that of insulating silicon carbide. Even if trace amounts of free silicon form a continuous phase in the filler network, it will cause a sharp decrease in the volume resistivity of the composite material, making it impossible to simultaneously meet the application requirements of high thermal conductivity and high insulation; in semiconductor wafer grinding and polishing applications, free silicon forms micro-batteries with the silicon carbide matrix or metal impurities, producing nanoscale pitting on the wafer surface, affecting device performance; in aluminum-based composite materials applications, free silicon reacts with the aluminum matrix to form a brittle Al-Si eutectic phase, leading to interface embrittlement.

[0003] In the prior art, Chinese patent application CN201810940508.8 discloses a method for preparing silicon carbide micro powder for silicon carbide fine ceramics. It uses a mixed flotation agent of paraffin oil and turpentine oil to remove free carbon, and combines acid washing and alkali washing steps for purification. However, this method places the particle shaping step before the purification step, and performs acid and alkali washing after shaping. There is a risk that the fresh surface introduced by shaping will reintroduce impurities in the subsequent purification process. In addition, this method does not involve surface modification treatment for high insulation and thermal conductivity applications, and cannot solve the problems of hard agglomeration caused by the high-energy surface of the highly purified particles and poor compatibility with organic matrices.

[0004] Currently, there is a lack of a systematic silicon carbide micropowder preparation scheme that can reduce the free silicon content to below 0.1 wt% while taking into account particle morphology control and surface functionalization treatment, so as to meet the stringent requirements of high-end application scenarios such as high insulation and thermal conductivity interface materials, high performance sintered ceramics and semiconductor processing.

[0005] Based on this, the present invention provides a low-free-silicon silicon carbide micro powder, its preparation method and application, to solve the above-mentioned technical problems. Summary of the Invention

[0006] The purpose of this invention is to provide a low-free-silicon silicon carbide micropowder, its preparation method, and its application, in order to solve the technical problems in the prior art, such as high free silicon content, irregular particle morphology, increased particle surface energy after high purification leading to hard agglomeration, and lack of systematic preparation schemes for high-end application scenarios such as insulation and thermal conductivity. As a result, it is impossible to simultaneously meet the stringent application requirements of multiple scenarios such as high insulation, high thermal conductivity, high-temperature sintering clean grain boundaries, and high-end semiconductor processing.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a low-free-silicon silicon carbide micro powder, wherein the silicon carbide micro powder contains a silicon carbide main phase and meets the following indicators: silicon carbide content not less than 98.5 wt%; free silicon content not more than 0.1 wt%; free carbon content not more than 0.1 wt%; and the particle surface of the silicon carbide micro powder is treated with a surface modifier.

[0009] By strictly controlling the free silicon content to below 0.1 wt%, the problem of decreased insulation caused by free silicon forming conductive pathways in the thermally conductive filler network as a semiconductor phase is eliminated. At the same time, the problem of decreased high-temperature strength caused by free silicon melting and forming grain boundary glass phase during high-temperature sintering is also eliminated. The particle surface is treated with a surface modifier to effectively reduce the high-energy surface activity exposed after high purification, inhibit the formation of hard agglomerates, and improve the dispersibility and interfacial compatibility of silicon carbide micropowder in the organic matrix.

[0010] Furthermore, the free silicon content does not exceed 0.05 wt%. Further reducing the free silicon content to below 0.05 wt% meets the requirements of high-end applications with more stringent insulation and surface cleanliness requirements, such as power semiconductor module potting and high-end wafer grinding and polishing.

[0011] Preferably, the silicon carbide content is not less than 99.5 wt%, and the total amount of metal impurities does not exceed 500 ppm; the metal impurities include at least one of iron, aluminum, calcium, and magnesium.

[0012] Further improve the purity of silicon carbide main phase and strictly control the total amount of metal impurities to effectively avoid the degradation of electrical performance caused by the diffusion of metal impurities on the semiconductor wafer surface, and meet the purity requirements of semiconductor-grade applications.

[0013] Specifically, the silicon carbide micropowder has an aspect ratio of no more than 2 and a particle morphology of nearly spherical or equal volume.

[0014] Near-spherical or equal-volume particles, compared to angular polygonal particles, exhibit better flowability and packing efficiency in high-filler thermally conductive composite systems. This helps maintain the processing flowability of the system at higher filler contents while reducing stress concentration points between particles.

[0015] In some embodiments, the particle size distribution of the silicon carbide micropowder satisfies D50 of 0.5 to 10 μm and D90 / D10 of no more than 4.

[0016] It is suitable for applications that require fine particle size and narrow particle size distribution, such as pressureless sintered silicon carbide ceramic raw materials and semiconductor wafer grinding and polishing media. Narrow particle size distribution helps to improve sintering density and grinding accuracy.

[0017] As a preferred embodiment, the particle size distribution of the silicon carbide micro powder satisfies D50 of 5 to 50 μm and D90 / D10 of no more than 5.

[0018] Suitable for high insulation and thermal conductivity interface materials, the larger particle size helps to build an effective thermal conductivity path under high filling volume. The D90 / D10 ratio of no more than 5 ensures the uniformity of particle size distribution and is conducive to the close packing of filler particles.

[0019] Preferably, the surface modifier is selected from at least one of silane coupling agents and titanate coupling agents.

[0020] Both silane coupling agents and titanate coupling agents can chemically react or physically adsorb with the hydroxyl groups on the surface of silicon carbide particles, forming an organic functional group layer on the particle surface, thereby reducing the particle surface energy, inhibiting hard agglomeration, and improving the interfacial bonding strength with the organic matrix.

[0021] This invention also provides a method for preparing low-free-silicon silicon carbide micro powder, comprising the following steps: mixing silicon carbide raw material with a flotation agent, performing flotation treatment to remove free carbon, filtering and collecting silicon carbide powder, washing with water until neutral, and drying to obtain a primary purified powder; adding the obtained primary purified powder to an acid washing solution, stirring and leaching at 20-80℃ for 1-6 hours to remove free silicon and metal impurities, filtering, washing with water until neutral, and drying to obtain a secondary purified powder; adding the obtained secondary purified powder to an alkaline washing solution. In a process involving stirring and leaching at 50–100°C for 1–4 hours to remove free silica, the powder is filtered, washed with water until neutral, and dried to obtain a three-stage purified powder. The obtained three-stage purified powder is then subjected to particle shaping treatment to reduce the aspect ratio of the particles to no more than 2, resulting in shaped powder. The shaped powder is then subjected to precise particle size classification to collect powders of the target particle size range. The obtained powders of the target particle size range are mixed with a surface modifier and subjected to surface modification treatment at 60–120°C to obtain the low-free-silicon silicon carbide micro powder.

[0022] The core of this preparation method lies in the use of a stepwise directional removal process based on the different chemical properties of various impurity phases (free carbon, free silicon, free silica, and metallic impurities) in silicon carbide micropowder. This process involves flotation to remove free carbon, acid washing to remove free silicon and metallic impurities, and alkali washing to remove free silica. Combined with particle shaping and surface modification treatment, this achieves the systematic elimination of impurity phases and the functionalization of particles.

[0023] First, flotation removes a large amount of free carbon, which can reduce the consumption of subsequent acid washing and prevent free carbon from coating the particles and affecting the acid washing efficiency; particle shaping is arranged after the purification step to avoid the introduction of impurities in subsequent chemical treatment by the fresh high-energy surface introduced by shaping; surface modification is carried out after precision classification to ensure the uniformity of particle size of the modified object.

[0024] Furthermore, in the flotation step, the flotation agent is a mixture of non-polar organic solvent and terpene solvent, and flotation continues until no more free carbon floats out of the slurry.

[0025] The mixture of nonpolar organic solvents and terpene solvents has a selective wetting effect on free carbon particles, causing free carbon to float to the surface preferentially, while silicon carbide particles settle due to their relatively strong hydrophilicity, thereby achieving efficient physical separation of free carbon and silicon carbide.

[0026] Preferably, in the pickling step, the pickling solution contains hydrofluoric acid and nitric acid; wherein the mass fraction of hydrofluoric acid is 5-40% and the mass fraction of nitric acid is 5-30%.

[0027] The mixed acid system of hydrofluoric acid and nitric acid has high dissolution efficiency for free silicon. Hydrofluoric acid reacts with silicon to form soluble fluorosilicic acid, while nitric acid provides oxidizing properties to accelerate the dissolution of metal impurities. Silicon carbide has good chemical stability in this acid system and is not corroded.

[0028] Specifically, in the alkaline washing step, the alkaline washing solution is a sodium hydroxide solution or a potassium hydroxide solution, and the mass fraction of alkali in the alkaline washing solution is 10-40%. Sodium hydroxide or potassium hydroxide solution can selectively dissolve free silicon dioxide (SiO2 + 2NaOH → Na2SiO3 + H2O), while silicon carbide has good chemical stability in alkaline solution, thereby achieving the directional removal of free silicon dioxide.

[0029] In some embodiments, the particle shaping step uses ball milling or airflow shaping, and the shaping time is 0.5 to 3 hours.

[0030] Ball milling shapes use the mechanical grinding action of grinding media on the edges of particles, while airflow shaping rounds the edges through high-speed collisions between particles. Both methods can reduce the aspect ratio of particles to no more than 2, resulting in near-spherical or equal-volume particle morphologies.

[0031] As a preferred embodiment, in the surface modification step, the surface modifier is a silane coupling agent, and its dosage is 0.1 to 2.0 wt% of the silicon carbide micro powder.

[0032] The dosage of silane coupling agent is in the range of 0.1 to 2.0 wt%, which can ensure the formation of a uniform organic functional group modified layer on the surface of silicon carbide particles, and avoid the effect of excessive coupling agent residue on the electrical and mechanical properties of composite materials.

[0033] Preferably, the prepared low-free-silicon silicon carbide micropowder has a free silicon content of no more than 0.05 wt% and a silicon carbide content of no less than 99.5 wt%. These preferred indicators reflect the high-end product quality level that this preparation method can achieve under strict control of process parameters, and can meet the most stringent purity requirements in application scenarios such as power semiconductor module potting.

[0034] This invention also provides the application of the above-mentioned low-free-silicon silicon carbide micropowder in the preparation of highly insulating and thermally conductive composite materials, wherein the volume resistivity of the highly insulating and thermally conductive composite material is not less than 10 Nm according to ASTM D257 standard. 12 Ω·cm, thermal conductivity not less than 3 W / (m·K) as determined by ASTM E1461 standard.

[0035] Low-free-silicon silicon carbide micropowder with a free silicon content of no more than 0.1 wt% is used as a thermally conductive filler, which eliminates the risk of semiconductor phase free silicon forming a conductive path in the filler network, enabling the composite material to maintain high volume resistivity while achieving high thermal conductivity, thereby breaking the technical bottleneck of the difficulty in achieving both high thermal conductivity and high insulation.

[0036] Furthermore, the low-free-silicon silicon carbide micropowder is used as a thermally conductive filler, with a filling amount of 50-90 wt% in the high-insulation and thermally conductive composite material; the high-insulation and thermally conductive composite material is used for potting power semiconductor modules or thermal pads.

[0037] High filler content (50-90 wt%) can form an effective thermal conductivity network between thermally conductive filler particles, achieving high thermal conductivity; the near-spherical or equal-volume particle morphology ensures that the system still has good processing flowability under high filler content, meeting the requirements of potting process.

[0038] The present invention also provides the application of the above-mentioned low free silicon silicon carbide micro powder in the preparation of pressureless sintered silicon carbide ceramics, wherein the particle size D50 of the silicon carbide micro powder is 0.5 to 10 μm, and it is used as a raw material powder for pressureless sintered silicon carbide ceramics.

[0039] Low free silicon content eliminates the risk of free silicon melting and forming a grain boundary glass phase during sintering. Fine grain size and narrow grain size distribution help improve sintering activity and sintered body density, thereby obtaining high-performance silicon carbide ceramics with clean grain boundaries.

[0040] Compared with the prior art, the beneficial effects of the present invention are:

[0041] 1. A step-by-step directional removal process is used to remove free carbon by flotation, free silicon and metal impurities by acid washing, and free silicon dioxide by alkaline washing. Each step is targeted at the chemical properties of different impurity phases to achieve directional removal. The process has strong synergy and reduces the free silicon content to below 0.1wt%, preferably to below 0.05wt%. Compared with the existing single acid washing or acid-alkali washing process, the impurity removal efficiency is higher and the product purity index is more stable, which meets the stringent purity requirements of various scenarios such as high insulation and thermal conductivity interface materials, high performance sintered ceramics and semiconductor processing.

[0042] 2. The particle shaping step is arranged after the purification step, which avoids the problem of impurities being reintroduced into the fresh high-energy surface introduced by the shaping in the existing technology during the subsequent chemical purification process. After shaping, the aspect ratio of the particles is reduced to no more than 2, and the morphology is close to spherical or equal volume. The fluidity and packing efficiency in the high-filling thermally conductive composite material system are significantly improved, which helps to maintain the processing fluidity of the system at a high filling content of 50-90wt%, while improving the efficiency of the construction of thermal conductive pathways between filler particles.

[0043] 3. Surface modification treatment is carried out after precision classification. For the high-energy Si and C atom surfaces exposed by high-purity silicon carbide particles, an organic functional group modification layer is formed on the particle surface by using silane coupling agents or titanate coupling agents. This effectively reduces the particle surface energy, inhibits the formation of hard agglomerates, and improves the dispersion uniformity and interfacial bonding strength of silicon carbide micro powder in the organic matrix. This solves the technical problem of defects in composite materials caused by hard agglomeration of high-purity silicon carbide micro powder due to high-energy surfaces. At the same time, the coupling agent itself does not introduce conductive impurities and does not affect the volume resistivity index of the composite material.

[0044] 4. The low-free-silicon silicon carbide micro powder provided by this invention fundamentally eliminates the semiconductor conductivity risk of free silicon, enabling silicon carbide micro powder to achieve a volume resistivity of not less than 10 Ω·cm when used as a thermally conductive filler at high filling amounts. 12 With high insulation and high thermal conductivity synergistic performance of Ω·cm and thermal conductivity of not less than 3W / (m·K), it breaks through the technical bottleneck of ordinary silicon carbide micropowder, which is difficult to achieve both high thermal conductivity and high insulation due to free silicon. It provides a reliable filler solution for high-end electronic packaging materials such as potting compounds for power semiconductor modules and thermal pads. Detailed Implementation

[0045] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0046] In this invention, the term "free silicon" refers to silicon in silicon carbide micropowder existing in the form of elemental silicon phase (Si), rather than chemically bonded silicon in silicon carbide. The term "free carbon" refers to carbon existing in the form of elemental carbon phase, including amorphous carbon and graphitic carbon. The term "free silica" refers to the oxide layer on the particle surface and the SiO2 phase remaining in the raw material.

[0047] In the following examples, the silicon carbide raw material used was industrial-grade green silicon carbide, purchased from a silicon carbide production enterprise in Ningxia. The raw material contained approximately 96-97 wt% SiC, approximately 0.3-0.5 wt% free silicon, and approximately 0.5-1.0 wt% free carbon.

[0048] Unless otherwise specified, all chemical reagents used are industrial grade. Hydrofluoric acid, nitric acid, and sodium hydroxide were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0049] The free silicon content was determined by the sodium hydroxide leaching method: silicon carbide powder was placed in a 30% NaOH solution and leached at 80°C for 4 hours. The free silicon reacted with NaOH to generate Na2SiO3 and dissolved. After filtration, the silicon content in the filtrate was determined by ICP-OES and converted into free silicon content.

[0050] Free carbon content was determined by combustion method;

[0051] The SiC content was calculated using the difference method;

[0052] The content of metal impurities was determined by ICP-OES (instrument model: Agilent 5100).

[0053] Particle size distribution was determined using a laser particle size analyzer (instrument model: Malvern Mastersizer3000).

[0054] The particle morphology was observed using a scanning electron microscope (instrument model: FEIQuanta250).

[0055] Thermal conductivity was determined using the laser flare method (instrument model: Netzsch LFA467), in accordance with ASTM E1461 standard;

[0056] Volume resistivity was measured using a high-resistivity meter (instrument model: Keysight B2987A) in accordance with ASTM D257 standard.

[0057] Example 1: Take 1000g of industrial-grade green silicon carbide raw material, add 2000mL of a mixed solvent of paraffin oil and turpentine oil (volume ratio 3:1), stir evenly and let stand. Free carbon floats preferentially on the liquid surface due to its hydrophobicity, while silicon carbide particles settle due to their strong hydrophilicity.

[0058] Repeat the above flotation operation until no more free carbon floats to the surface of the slurry. Filter and collect the settled silicon carbide powder, wash with deionized water until the pH of the washing solution is neutral, and dry in an oven at 120°C for 12 hours to obtain approximately 960g of purified powder.

[0059] 960g of the purified powder was added to 4000mL of a mixed pickling solution containing hydrofluoric acid (20% by mass) and nitric acid (15% by mass), and stirred and leached at 50℃ for 3h. During the pickling process, free silicon reacted with hydrofluoric acid to form soluble fluorosilicic acid and dissolved out, while metallic impurities reacted with nitric acid and dissolved into the acid solution.

[0060] After acid washing, the powder was filtered, washed with deionized water until the pH of the washing solution was neutral, and dried at 120℃ for 12 hours to obtain approximately 950g of secondary purified powder.

[0061] 950g of the purified powder was added to 3000mL of a 20% sodium hydroxide solution and stirred at 80℃ for 2 hours. The sodium hydroxide solution selectively dissolved free silicon dioxide (SiO2 + 2NaOH → Na2SiO3 + H2O). Silicon carbide exhibits good chemical stability in alkaline solutions and is not corroded.

[0062] After alkaline washing, the powder was filtered, washed with deionized water until the pH of the washing solution was neutral, and dried at 120℃ for 12 hours to obtain approximately 940g of three-stage purified powder.

[0063] 940g of the three-stage purified powder was added to a ball mill, using alumina balls as the grinding medium at a ball-to-powder ratio of 3:1 and a rotation speed of 60 r / min for 1.5 h. During the shaping process, the grinding medium mechanically ground the edges of the particles, reducing their aspect ratio. After shaping, scanning electron microscopy revealed that the particle morphology changed from sharp polygons to near-spherical or isotropic shapes, with an aspect ratio not exceeding 2, yielding approximately 930g of shaped powder.

[0064] 930g of shaped powder was fed into an air classifier. After adjusting the classification parameters, approximately 600g of powder with a target particle size range (D50) of 5–15 μm was collected. Laser particle size analyzer measurements showed: D50 = 8.2 μm, D90 / D10 = 3.6.

[0065] Add 600g of the target particle size powder to a high-speed mixer, add 6g of γ-aminopropyltriethoxysilane (KH-550) (accounting for 1.0wt% of the mass of silicon carbide micro powder), and mix at 100℃ for 30min to form an organic functional group modified layer on the surface of silicon carbide particles with silane coupling agent, and obtain approximately 604g of low free silicon silicon carbide micro powder product;

[0066] The obtained product was characterized, and the results are as follows: SiC content 99.1 wt%; free silicon content 0.08 wt%; free carbon content 0.05 wt%; total metal impurities (Fe+Al+Ca+Mg) 380 ppm; D50=8.2 μm, D90 / D10=3.6; particle aspect ratio not exceeding 2, and morphology nearly spherical.

[0067] Example 2 follows the same preparation method as Example 1, except that the mass fraction of hydrofluoric acid is increased to 30%, the mass fraction of nitric acid is increased to 20%, the pickling temperature is increased to 70°C, the pickling time is extended to 5 hours, and the pickling operation is repeated once (a total of two picklings) to further dissolve residual free silicon. The remaining flotation, alkali washing, shaping, classification, and surface modification steps are the same as in Example 1.

[0068] The obtained product was characterized, and the results are as follows: SiC content 99.6 wt%; free silicon content 0.04 wt%; free carbon content 0.04 wt%; total metal impurities (Fe+Al+Ca+Mg) 280 ppm; D50=8.5 μm, D90 / D10=3.5; particle aspect ratio not exceeding 2, and morphology nearly spherical;

[0069] The above results show that by strengthening the pickling conditions and increasing the number of pickling cycles, the free silicon content can be further reduced to below 0.05 wt%, the SiC content can be increased to above 99.5 wt%, and the total amount of metal impurities can be reduced to below 300 ppm, meeting the stringent purity requirements of high-end application scenarios such as power semiconductor module potting.

[0070] Example 3 follows the same preparation method as Example 1, with all purification steps (flotation, acid washing, alkali washing) and shaping steps identical to Example 1. The difference lies in adjusting the airflow classification parameters in the classification step, collecting approximately 500g of powder with a target particle size range of 10–30 μm (D50). Laser particle size analyzer results: D50 = 18.6 μm, D90 / D10 = 4.2. The surface modification step is the same as in Example 1, with KH-550 added at 0.8 wt% of the silicon carbide micropowder mass.

[0071] The obtained silicon carbide micro powder product was characterized as follows: SiC content 99.0 wt%; free silicon content 0.07 wt%; free carbon content 0.05 wt%; D50 = 18.6 μm, D90 / D10 = 4.2; particle aspect ratio not exceeding 2.

[0072] The above-mentioned silicon carbide micro powder was filled into a bisphenol A type epoxy resin matrix (the curing agent was methylhexahydrophthalic anhydride and the accelerator was 2-ethyl-4-methylimidazolium) at a filling amount of 75 wt%. After being mixed evenly, it was pre-cured at 100℃ for 2 h and then cured at 150℃ for 4 h to prepare a thermally conductive composite material sample.

[0073] Performance tests were performed on the thermally conductive composite material samples: thermal conductivity (laser flare method, ASTM E1461) was 4.8 W / (m·K); volume resistivity (ASTM D257) was 3.2 × 10⁻⁶. 13 Ω·cm. The above results show that the low free silicon silicon carbide micropowder obtained in this embodiment, with a high filling content of 75wt%, simultaneously satisfies the requirements of a thermal conductivity of not less than 3W / (m·K) and a volume resistivity of not less than 10Ω·cm. 12 High insulation and high thermal conductivity requirements (Ω·cm).

[0074] Example 4 follows the same preparation method as Example 1, with all purification and shaping steps identical to those in Example 1. The difference lies in adjusting the airflow classification parameters in the classification step, collecting approximately 400g of fine-particle-size powder with a D50 of 1–5 μm. Laser particle size analyzer measurements showed D50 = 2.8 μm and D90 / D10 = 3.2. The surface modification step was the same as in Example 1, but the amount of KH-550 added was 1.5 wt% of the silicon carbide micropowder mass.

[0075] The obtained silicon carbide micro powder product was characterized as follows: SiC content 99.2 wt%; free silicon content 0.07 wt%; free carbon content 0.04 wt%; total metal impurities 320 ppm; D50 = 2.8 μm, D90 / D10 = 3.2; particle aspect ratio not exceeding 2.

[0076] The above-mentioned fine-particle-size silicon carbide micro powder was mixed evenly with sintering aids (0.5wt% boron carbide and 2.0wt% carbon black), and after spray granulation, it was cold isostatically pressed at 200MPa and sintered without pressure at 1900℃ under argon atmosphere for 2h to prepare silicon carbide ceramic samples.

[0077] The sintered ceramic samples were characterized: the relative density was 98.2% as determined by the Archimedes method; the three-point flexural strength at room temperature was 420 MPa; and the grain boundary morphology was observed by scanning electron microscopy, showing clean grain boundaries and no obvious glassy phase. These results indicate that low-free-silicon silicon carbide micropowder effectively eliminates the risk of free silicon melting and forming a glassy phase at grain boundaries during sintering, contributing to the acquisition of silicon carbide ceramics with high density, high strength, and clean grain boundaries.

[0078] Example 5 follows the same preparation method as Example 1, with flotation, acid washing, alkali washing, shaping, and classification steps. After classification, approximately 600g of powder with a target particle size of 5–15μm (D50) was collected. The difference lies in the surface modification step, where the silane coupling agent KH-550 was replaced with a titanate coupling agent (isopropyltrioleoyloxytitanate, KR-TTS), at an amount of 1.2wt% of the silicon carbide micropowder mass, and the mixture was treated at 100°C for 30min.

[0079] The obtained product was characterized as follows: SiC content 99.0 wt%; free silicon content 0.08 wt%; free carbon content 0.05 wt%; D50 = 8.4 μm, D90 / D10 = 3.7; particle aspect ratio not exceeding 2.

[0080] The obtained product was filled into an epoxy resin matrix at a filler content of 75 wt% to prepare a thermally conductive composite material. The testing method was the same as in Example 3.

[0081] The thermal conductivity is 4.6 W / (m·K); the volume resistivity is 2.8 × 10⁻⁶. 13 Ω·cm. The results show that surface modification using titanate coupling agents can also achieve surface functionalization of silicon carbide particles. The thermal conductivity and insulation properties of the resulting composite material are comparable to those of Example 3, verifying that surface modifiers selected from silane coupling agents and titanate coupling agents can achieve the technical effects of this invention.

[0082] Comparative Example 1: 1000g of industrial-grade green silicon carbide raw material was taken and directly added to 4000mL of a mixed pickling solution containing hydrofluoric acid (20% by mass) and nitric acid (15% by mass) without flotation to remove free carbon. The solution was stirred and leached at 50℃ for 3 hours, filtered, washed with deionized water until neutral, and dried at 120℃ for 12 hours to obtain pickled powder. Without alkaline washing, the pickled powder was directly ball-milled (parameters same as in Example 1) and air-classified, collecting powder with a D50 of 5–15μm without surface modification.

[0083] The obtained powder was characterized as follows: SiC content 97.8 wt%; free silicon content 0.12 wt%; free carbon content 0.35 wt%; free silica content approximately 0.8 wt%; total metal impurities 680 ppm; D50 = 8.0 μm; D90 / D10 = 4.5.

[0084] The comparison between Example 1 and Comparative Example 1 shows that the lack of a flotation step resulted in a free carbon content as high as 0.35 wt% (0.05 wt% in Example 1). This is because the free carbon coats the surface of the particles, hindering the contact between the acid and the free silicon, thus reducing the free silicon removal efficiency (free silicon content of 0.12 wt%, higher than 0.08 wt% in Example 1). The lack of an alkaline washing step resulted in a free silica residue of about 0.8 wt% and a SiC content of only 97.8 wt%, with an overall purity significantly lower than that of Example 1. This demonstrates the necessity of a multi-step ordered purification process combination compared to a single acid washing.

[0085] Comparative Example 2 used commercially available ordinary green silicon carbide micro powder, without processing by the preparation method of this invention. A commercially available product with a D50 of approximately 18 μm was directly taken and characterized: SiC content 97.2 wt%; free silicon content 0.28 wt%; free carbon content 0.42 wt%; total metal impurities 1200 ppm; D50 = 18.3 μm; D90 / D10 = 5.8; particle morphology was a polygonal shape with distinct edges.

[0086] Commercially available ordinary silicon carbide micropowder was added at a filler content of 75 wt% to an epoxy resin matrix with the same formulation as in Example 3 to prepare a thermally conductive composite material sample. The testing method was the same as in Example 3. The thermal conductivity was 3.9 W / (m·K); the volume resistivity was 8.6 × 10⁻⁶. 9 Ω·cm;

[0087] A comparison of Example 3 and Comparative Example 2 shows that commercially available ordinary silicon carbide micropowder has a high free silicon content of 0.28 wt%. This free silicon acts as a semiconductor phase, forming conductive pathways in the filler network, resulting in a composite material with a volume resistivity of only 8.6 × 10⁻⁶. 9 The Ω·cm is about three orders of magnitude lower than that of Example 3, which fails to meet the requirement of a volume resistivity of not less than 10 Ω·cm. 12 The high insulation requirement of Ω·cm demonstrates the decisive role of free silicon content control in maintaining the insulation performance of composite materials, an effect that was unexpected.

[0088] Comparative Example 3, following the preparation method of Example 1, involved the same flotation, acid washing, alkali washing, shaping, and classification steps as Example 1. After classification, approximately 600g of powder with a target particle size range of 5–15 μm was collected. The difference was that the surface modification step was omitted, and no surface modifier was added; the classified powder was directly used as the final product.

[0089] The obtained powder was characterized as follows: SiC content 99.1 wt%; free silicon content 0.08 wt%; free carbon content 0.05 wt%; D50 = 8.3 μm; D90 / D10 = 3.6.

[0090] The unmodified silicon carbide micropowder was added to an epoxy resin matrix with the same formulation as in Example 3 at a loading of 75 wt%. During mixing, significant agglomeration was observed, and the mixture exhibited poor flowability and was difficult to disperse uniformly. Thermally conductive composite material samples were prepared, and the testing methods were the same as in Example 3. The thermal conductivity was 3.8 W / (m·K); the volume resistivity was 1.5 × 10⁻⁶. 12 Ω·cm;

[0091] Scanning electron microscopy revealed obvious aggregates of silicon carbide particles in the cross-section of the composite material. The presence of voids within these aggregates resulted in discontinuous thermal conductivity pathways, leading to a lower thermal conductivity than in Example 3 (4.8 W / (m·K)). A comparison between Example 3 and Comparative Example 3 shows that the surface modification step, by forming an organic functional group layer on the particle surface, effectively suppressed the hard agglomeration induced by the high-energy surface of the highly purified silicon carbide particles, resulting in uniform dispersion of the particles within the organic matrix. This increased the thermal conductivity by approximately 26%, demonstrating the significant contribution of the surface modification step to improving the performance of the composite material.

[0092] Test Example 1 summarizes and compares the main purity indicators of silicon carbide micropowders obtained from Examples 1 to 5 and Comparative Examples 1 to 3. The results are shown in Table 1.

[0093] Table 1 Comparison of purity indices of silicon carbide micropowder in each embodiment and comparative example.

[0094] Sample source SiC content (wt%) Free silicon content (wt%) Free carbon content (wt%) Total metallic impurities (ppm) D50 (μm) D90 / D10 Example 1 99.1 0.08 0.05 380 8.2 3.6 Example 2 99.6 0.04 0.04 280 8.5 3.5 Example 3 99.0 0.07 0.05 390 18.6 4.2 Example 4 99.2 0.07 0.04 320 2.8 3.2 Example 5 99.0 0.08 0.05 400 8.4 3.7 Comparative Example 1 97.8 0.12 0.35 680 8.0 4.5 Comparative Example 2 97.2 0.28 0.42 1200 18.3 5.8 Comparative Example 3 99.1 0.08 0.05 380 8.3 3.6

[0095] Test Example 2 summarizes and compares the thermal conductivity and volume resistivity of the thermally conductive composite materials (all with a filler content of 75 wt%) prepared in Examples 3, 5, Comparative Example 2 and Comparative Example 3. The results are shown in Table 2.

[0096] Table 2 Comparison of the performance of thermally conductive composite materials in each embodiment and comparative example.

[0097] Sample source Thermal conductivity (W / (m·K)) Volume resistivity (Ω·cm) Does it meet the requirements for high insulation and high thermal conductivity? Example 3 4.8 <![CDATA[3.2×10 13 ]]> yes Example 5 4.6 <![CDATA[2.8×10 13 ]]> yes Comparative Example 2 3.9 <![CDATA[8.6×10 9 ]]> No (insufficient insulation) Comparative Example 3 3.8 <![CDATA[1.5×10 12 ]]> Barely acceptable (low thermal conductivity)

[0098] As shown in Table 2, the thermal conductivity of the thermally conductive composite materials obtained from the low-free-silicon silicon carbide micropowders in Examples 3 and 5, with a high filling content of 75 wt%, is not less than 4.6 W / (m·K), and the volume resistivity is not less than 2.8 × 10⁻⁶. 13 Ω·cm, simultaneously meeting the application requirements of high thermal conductivity and high insulation. Comparative Example 2, due to excessive free silicon content, has a volume resistivity of only 8.6 × 10⁻⁶ Ω·cm. 9The thermal conductivity of Example 3 is only 3.8 W / (m·K) due to the lack of surface modification and particle agglomeration, which is significantly lower than that of Example 3.

[0099] It is understood that the flotation agent is not limited to a mixture of paraffin oil and turpentine oil, but can also be a combination of other non-polar organic solvents and terpene solvents, as long as it can selectively wet free carbon particles and achieve the physical separation of free carbon and silicon carbide.

[0100] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0101] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-free-silicon silicon carbide micro powder, characterized in that, The silicon carbide micro powder comprises a silicon carbide main phase, wherein the silicon carbide content of the main phase is not less than 98.5 wt%, the free silicon content is not more than 0.1 wt%, the free carbon content is not more than 0.1 wt%, the aspect ratio of the silicon carbide micro powder is not more than 2, the particle morphology of the silicon carbide micro powder is nearly spherical or equal volume, the particle size distribution D90 / D10 of the silicon carbide micro powder is not more than 5, and the particle surface of the silicon carbide micro powder is treated with at least one of silane coupling agent or titanate coupling agent.

2. The low-free-silicon silicon carbide micro powder according to claim 1, characterized in that: The free silicon content does not exceed 0.05 wt%; the silicon carbide content is not less than 99.5 wt%; the total amount of metal impurities does not exceed 500 ppm, and the metal impurities include at least one of iron, aluminum, calcium, and magnesium.

3. The low-free-silicon silicon carbide micro powder according to claim 1, characterized in that: The particle size distribution of the silicon carbide micro powder satisfies either D50 of 5 to 50 μm or D50 of 0.5 to 10 μm and D90 / D10 not exceeding 4.

4. A method for preparing low-free-silicon silicon carbide micropowder as described in any one of claims 1 to 2, characterized in that, Includes the following steps: (1) Mix silicon carbide raw material with flotation agent, perform flotation treatment to remove free carbon, filter and collect silicon carbide powder, wash with water until neutral and dry to obtain primary purified powder; (2) Add the first-purified powder obtained in step (1) into the acid washing solution, stir and leach at 20-80℃ for 1-6 hours to remove free silicon and metal impurities, filter and wash with water until neutral, dry to obtain the second-purified powder; (3) Add the secondary purified powder obtained in step (2) into the alkaline washing solution, stir and leach at 50-100℃ for 1-4 hours to remove free silica, filter and wash with water until neutral, dry to obtain the tertiary purified powder; (4) The three-stage purified powder obtained in step (3) is subjected to particle shaping treatment to reduce the aspect ratio of the particles to no more than 2, thereby obtaining shaped powder; (5) Perform precision particle size classification on the shaped powder obtained in step (4) and collect the powder of the target particle size range; (6) The target particle size powder obtained in step (5) is mixed with a surface modifier and surface modified at 60-120°C to obtain the low free silicon silicon carbide micro powder.

5. The preparation method according to claim 4, characterized in that: In step (1), the flotation agent is a mixture of non-polar organic solvent and terpene solvent, and flotation continues until no more free carbon floats out of the slurry; in step (2), the pickling solution contains hydrofluoric acid and nitric acid, wherein the mass fraction of hydrofluoric acid is 5-40% and the mass fraction of nitric acid is 5-30%; in step (3), the alkaline washing solution is a sodium hydroxide solution or a potassium hydroxide solution, wherein the mass fraction of alkali in the alkaline washing solution is 10-40%.

6. The preparation method according to claim 4, characterized in that: In step (4), the particle shaping process is performed by ball milling or airflow shaping, and the shaping time is 0.5 to 3 hours. In step (6), the surface modifier is a silane coupling agent, and its dosage is 0.1 to 2.0 wt% of the mass of silicon carbide micro powder.

7. The preparation method according to claim 4, characterized in that: The prepared low-free-silicon silicon carbide micro powder contains no more than 0.05 wt% free silicon and no less than 99.5 wt% silicon carbide.

8. The application of the low-free-silicon silicon carbide micropowder as described in claim 1 or 2 in the preparation of highly insulating and thermally conductive composite materials, wherein the volume resistivity of the highly insulating and thermally conductive composite material, as determined by ASTM D257 standard, is not less than 10 Ω·cm. 12 Ω·cm, thermal conductivity not less than 3 W / (m·K) as determined by ASTM E1461 standard.

9. The application as described in claim 8, characterized in that: The low-free-silicon silicon carbide micropowder is used as a thermally conductive filler, and its filling amount in the high-insulation and thermally conductive composite material is 50-90 wt%; the high-insulation and thermally conductive composite material is used for potting power semiconductor modules or thermal pads.

10. The application of the low free silicon silicon carbide micro powder as described in claim 1 or 2 in the preparation of pressureless sintered silicon carbide ceramics, wherein the particle size D50 of the silicon carbide micro powder is 0.5 to 10 μm, and it is used as a raw material powder for pressureless sintered silicon carbide ceramics.

Citation Information

Patent Citations

  • Preparation method for silicon carbide micropowder for fine silicon carbide ceramic

    CN108752003A

  • Method of preparing silicon carbide micropowder

    CN107522203A

  • Preparation method of silicon carbide micropowder

    CN107522493A